MEDIAL AND LATERAL PERCUTANEOUS FIXATION VERSUS LATERAL FIXATION FOR TREATMENT OF GARTLAND TYPE II, III SUPRACONDYLAR FRACTURE OF HUMERUS IN CHILDREN (Iraqi Journal of Medical Sciences, 2016)
Background:Operative treatment of supracondylar fractures with reduction and percutaneous pinning is so effective and safe. The great majority of displaced fractures should be treated operatively. There is little controversy that all closed Gartland type II and III fractures should have an attempt at closed reduction and pinning.Objective:To compare the efficacy of medial and lateral entry pinning with lateral entry pinning for percutaneous fixation of displaced (Gartland type II and III) extension type supracondylar fractures of the humerus in children.Methods: A prospective study conducted at a single centre from December 2008 to November 2011. Eighty patients who satisfied the inclusion and exclusion criteria were enrolled in the study, with 40 patients in each group. All the pinning was done according to a uniform standardized technique. The patients were re-evaluated as outpatients at three weeks, six weeks and three months after the surgery.Results:No significant differences were found between the two groups with regard to base-line characteristics, withdrawals, complication rate and various outcome measures such as carrying angle, passive range of elbow motion, Flynn grading, Baumanns angle, change in the Baumann angle and loss of reduction grading.Conclusions:If a uniform standardized operative technique is followed in each method, then the result of both methods will be same in terms of safety and efficacy.Keywords :Supracondylar fractures, Humerus, Children, Percutaneous fixation